PENGARUH VARIETAS DAN APLIKASI TEKNOLOGI BUDI DAYA TERHADAP KUALITAS UMBI BAWANG PUTIH - Suwarni Tri Rahayu; Rofik Sinung Basuki; Poetry Sari Levianny (Widyariset, 2020)
Garlic demand in Indonesia currently still depends on import supply due to the low rate of production and its quality still inadequate to fulfill the consumer’s request who demand a bigger size. Therefore, the government has been developing garlic innovative cultivation technology, namely TIBBP, which expected to increase local garlic quality. This research aims to compare and identify the influence of TIBBP and farmer’s conventional cultivation technology and to compare the potential of garlic local variety, Lumbu Hijau and Tawangmangu Baru, on garlic bulb quality. This research was conducted in Tawangmangu, Karanganyar, Central Java. The result showed that TIBBP has been proven to increase garlic bulb quality compared to the farmer’s conventional technology. Tawangmangu Baru which cultivated with TIBBP has 32.69% bigger diameter and 11.5 gram heavier compared to Tawangmangu Baru which cultivated with the farmer’s conventional technology. Tawangmangu Baru proximate composition cultivated with TIBBP also showed better value compared to the farmer’s conventional technology. In general Tawangmangu Baru was also superior compared to Lumbu Hijau. This TIBBP might be disseminated and implemented broadly to increase garlic bulb quality in Indonesia.